2021
DOI: 10.1155/2021/5549893
|View full text |Cite
|
Sign up to set email alerts
|

The Escalating Magnitude of COVID-19 Infections among the Northeastern Ethiopia Region: A Community-Based Cross-Sectional Study

Abstract: Background. The novel coronavirus disease (COVID-19) is lethal and extremely contagious, with a rapidly rising global prevalence. The World Health Organization has declared the outbreak a global pandemic; it is reported to have spread to nearly every country in the world. However, the prevalence varies across developed and developing countries, as well as within different regions of the same country. It is not hidden that estimating the magnitude of COVID-19 infection from the community surveys is critical for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 38 publications
(53 reference statements)
0
3
1
Order By: Relevance
“…This finding was comparable to a county-based random sample study in Indiana 17 that reported a seroprevalence of 1.74%. However, the finding was lower than studies in Northeastern Ethiopia, 18 the Oromia region, 19 and Addis Ababa 12 detecting a COVID-19 prevalence of 3.3%, 5.5%, and 3.5%, respectively. Similarly, this finding was lower than population-based studies done in California 20 and Brazil, 9 which reported a seroprevalence of 4.7% and 2.1%, respectively.…”
Section: Discussioncontrasting
confidence: 72%
“…This finding was comparable to a county-based random sample study in Indiana 17 that reported a seroprevalence of 1.74%. However, the finding was lower than studies in Northeastern Ethiopia, 18 the Oromia region, 19 and Addis Ababa 12 detecting a COVID-19 prevalence of 3.3%, 5.5%, and 3.5%, respectively. Similarly, this finding was lower than population-based studies done in California 20 and Brazil, 9 which reported a seroprevalence of 4.7% and 2.1%, respectively.…”
Section: Discussioncontrasting
confidence: 72%
“…The mortality from the disease within a country is also high, with an estimated 3174 deaths attributed to the disease [4,5]. However, the total number of cases detected in Ethiopia may have been underestimated because of insufficient testing capacity [6].…”
Section: Introductionmentioning
confidence: 99%
“…Many people, including Ethiopian long-distance vehicle drivers, traders, and others, have been traveling from Djibouti to Ethiopia via the route that connects the Amhara area, Addis Ababa, and Oromia region since the commencement of the COVID-19 pandemic, mostly owing to geographical proximity (32) SARS-CoV 2 infection is very dangerous for certain populations.…”
Section: Resultsmentioning
confidence: 99%